Hi!
I'm having some trouble understanding how I'm supposed to use the reduction and deduction methods.
The question is:
(p → q) ∧ (¬p → r) ∧ ((¬p ∧ r) → s) ∧ ¬q ⇒ s
Prove that this is correct, with the deduction AND reduction method.
I'm fairly new to this kind mathematics, so if somebody could explain and guide me through the answer I would be really grateful!
PS: Excuse the bad grammar (if any), english is my fourth language.
Thanks in advance.
Greetings!
I'm having some trouble understanding how I'm supposed to use the reduction and deduction methods.
The question is:
(p → q) ∧ (¬p → r) ∧ ((¬p ∧ r) → s) ∧ ¬q ⇒ s
Prove that this is correct, with the deduction AND reduction method.
I'm fairly new to this kind mathematics, so if somebody could explain and guide me through the answer I would be really grateful!
PS: Excuse the bad grammar (if any), english is my fourth language.
Thanks in advance.
Greetings!